Factors Influencing Sustainability of Non-Governmental Organizations in the developing world - Kanwal Gul; Swapnil Morande (SEISENSE Business Review, 2023)
NGOs provide support services in developing countries when governments are unable to improve the growth indicators. There exists a requirement for sustainable NGOs that can help fill the gap between the needs of the people and the scarce resources available in developing countries. This study aimed to identify essential factors that are internally controllable by the NGO and to reflect on the impact of the internally controllable factors on the NGO’s sustainability. The study used established theories to investigate internal and external factors influencing NGOs and to identify the factors of significance. This qualitative research was designed with a systematic review followed by content analysis. It was undertaken in a developing country with a sample size of thirty-four using Purposive sampling. Analysis suggests that three variables including Financial Performance, Organizational Practices, and Community Interest have a statistically significant effect on sustainability. The study infers that considering the business environment, NGOs must focus on internal controllable factors. It also reiterates that NGOs should ensure a steady flow of funds, have robust management and should enjoy the support of the community to remain sustainable.